Genome editing of SlMYB3R3, a cell cycle transcription factor gene of tomato, induces elongated fruit shape. (7th September 2022) - Zheng, Qingyou; Takei-Hoshi, Rie; Okumura, Hitomi; Ito, Masaki; Kawaguchi, Kohei; Otagaki, Shungo; Matsumoto, Shogo; Luo, Zhengrong; Zhang, Qinglin; Shiratake, Katsuhiro
Abstract: Fruit shape is an important trait that attracts consumers, and the regulation of genes related to cell division is crucial for shaping multicellular organs. In Arabidopsis, MYB3R transcription factors, which harbor three imperfect repeats in the N-terminus, control organ growth by regulating cell division. However, the function of MYB3Rs in tomato remains unknown. Here, we characterized tomato SlMYB3R3, which was preferentially expressed in flowers and placed in a subclade with two Arabidopsis cell cycle suppressors ( MYB3R3/5 ) . slmyb3r3 knockout mutants were generated using the CRISPR/Cas9 system. Morphological observation of the slmyb3r3 mutants showed that fruits that were elongated and occasionally peanut-like in shape were formed, which was caused by significantly increased cell numbers in the longitudinal direction. Transcriptome and yeast one-hybrid assay results suggested that SlMYB3R3 acted as a suppressor of cell-cycle-related genes by binding to the mitosis-specific activator (MSA) motifs in their promoters. Taken together, knock out of the suppressor SlMYB3R3 leads to elongated fruit, which results from the altered cell division pattern at the ovary stage, by regulating cell-cycle-related genes in an MSA-dependent manner. Our results suggest that SlMYB3R3 and its orthologs have the potential to change fruit shape as part of the molecular breeding of fruit crops. Abstract : Knock out of SlMYB3R3 alters the cell division pattern in tomato ovary and leads to elongated fruits by regulating cell-cycle-related genes at the ovary stage in an MSA-dependent manner.